MULTIPLE CONGENITAL CONTRACTURES (ARTHROGRYPOSIS MULTIPLEX CONGENITA) - Canan Çınar,; Melek Sezgin,; Ece Aydoğ,; Aytül Çakcı, (Archives of Rheumatology, 2004)
Arthrogryposis multiplex congenita (AMC) is a term that is used to describe the presence of multiple joint contractures that are present at birth. It can be seen in isolation or in association with other congenital abnormalities as part of a syndrome with or without central nervous system involvement. The exact pathogenesis of arthrogryposis is unknown. The common factor causing congenital arthrogryposis is lack of fetal movements. It may be due to a large number of disorders. They may be neuropatic, affecting the brain, the spinal cord, or the peripheral nerves; they may be abnormalities of the muscles; they may be diseases of the connective tissues; or they may be conditions which limit the space within the uterus; they may result from abnormal intrauterin environment. Trying to define a cause is important to give reliable genetic advice to the parents and also to establish a prognosis. Treatment must be by physiotherapy, splinting, serial casting and by orthopedic surgery. Physical therapy is a lifelong process and should be initiated early in the neonatal period. The purpose of this article is to provide an overview of the AMC syndrome, specifically, clinical features, etiology, classification, diagnosis, therapeutic intervention and prognosis.